Analysis of Value for Money and Accountability in Improving Public Services At The Makassar City Water Corporation - Andi Annisa Rahma Makmur (JEKAMI Journal of Accounting, 2022)
This research is a qualitative descriptive study with the aim of knowing the analysis of the concept of Value for Money and accountability in improving public services at The Makassar City Water Corporation. This research was conducted at the Makassar City Water Supply Corporation office. In this study, the data sources used are primary and secondary data. The data used in this study is qualitative data obtained from observations, interviews and documentation results. The data collection technique of this research was carried out in 3 ways, namely observation, interview and documentation techniques. The research instrument is the researcher himself, interview guide, and a recording device. Value for Money can be said to be good if it meets three elements, namely economy, efficiency, and effectiveness. The Makassar City Water Supply Corporation has fulfilled these three elements in order to improve the quality of existing services. The accountability applied to the Makassar City Water Supply Corporation is quite good because the company has been able to swiftly and responsively handle problems that occur in the field as quickly as possible. Based on the results of the research that has been done, this analysis shows that the application of the concept of value for money and accountability in the company has been done well to improve the existing public services at the Makassar City Water Corporation